Expression of lncRNAs NEAT1 and lnc-DC in Serum From Patients With Behçet’s Disease Can Be Used as Predictors of Disease - Mohammed, Shereen Rashad; Abdelaleem, Omayma O.; Ahmed, Fatma A.; Abdelaziz, Ahmed Ali; Hussein, Hoda Abdelbadie; Eid, Hanaa M.; Kamal, Marwa; Ezzat, Mostafa Ahmed; Ali, Marwa A. (Frontiers in Molecular Biosciences, 2022)
Abstract Background. Behçet’s disease (BD) is a chronic autoimmune disease. Early diagnosis of BD is very important to avoid serious and/or fatal complications such as eye damage, severe neurological involvement, and large vessel occlusion. New, sensitive biomarkers would aid in rapid diagnosis, monitoring of disease activity, and response to treatment. Methods. This study’s aim is to identify two immune system related BD biomarkers. We measured long non-coding RNAs (lncRNAs) NEAT1(nuclear enriched abundant transcript 1) and lnc-DC (lncRNA in dendritic cells) in serum by real-time polymerase chain reaction (RT-PCR) in 52 BD patients and 52 controls. We analyzed the association between NEAT1 and lnc-DC and clinical parameters of BD. Receiver operating characteristic (ROC) curve analysis was performed to explore the diagnostic performance of the studied genes. Results. Compared to controls, significant upregulation of NEAT1 (Median (IQR) = 1.68 (0.38–7.7), p < 0.0001) and downregulation of lnc-DC (Median (IQR) = 0.2 (0.12–1.39), p = 0.03) were detected in the sera collected from BD patients. Higher serum expression levels of NEAT1 and lnc-DC were significantly associated with the following clinical presentations: cutaneous lesions, vascular manifestations, articular manifestations, neurological manifestations, and higher disease activity score. Also, high NEAT1 levels were significantly associated with a negative pathergy test, while higher lnc-DC was significantly associated with a positive family history. ROC curves showed that NEAT1 and lnc-DC levels in serum could be used as predictors of BD with high specificity and fair sensitivity. NEAT1 had an area under the curve (AUC) of 0.692 (95 % CI: 0.591–0.794, p = 0.001), and lnc-DC had an AUC of 0.615 (95 % CI: 0.508–0.723, p = 0.043). Conclusions. Serum lncRNAs NEAT1and lnc-DC are biomarkers for BD.